2023
DOI: 10.1557/s43580-023-00568-4
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of the thermodynamic and magnetic properties of Co-alloyed MnPt

Abstract: Magnetic functional materials remain an area of research interest for applications in electronic devices. Among these materials, Mn50Pt50 alloy has received a great deal of attention in practical potential applications such as spintronics due to its high-thermal and magnetic stability. It was reported previously that L10 Mn50Pt50 alloy shows ferromagnetic ordering at room temperature. In this study, the effect of the partial substitution of Pt with Co was investigated using density functional theory (DFT) appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Titanium cluster simulation studies conducted at the pilot plant facility at the CSIR have given valuable insights on titanium metal growth [48]. Recent studies have been extended to magnets [49], including where machine learning cluster expansion methods were employed to find ductile high saturation magnetization and Curie temperature alloys [50].…”
Section: Alloy Developmentmentioning
confidence: 99%
“…Titanium cluster simulation studies conducted at the pilot plant facility at the CSIR have given valuable insights on titanium metal growth [48]. Recent studies have been extended to magnets [49], including where machine learning cluster expansion methods were employed to find ductile high saturation magnetization and Curie temperature alloys [50].…”
Section: Alloy Developmentmentioning
confidence: 99%
“…The L1 0 phase was preferred over the B2 phase by both Fe and Cr on the Mn-site, as demonstrated by the thermodynamic and mechanical stability. Furthermore, in another study, we investigated the effect of ferromagnetic element (Co) on the magnetic properties of Mn 50 Pt 50 alloy using the same theoretical approach [17]. The findings indicated that because of the negative heats of formation, the addition of Co favored L1 0 over the B2 phase.…”
Section: Introductionmentioning
confidence: 99%